Persepsi Mahasiswa Pendidikan Guru Sekolah Dasar terhadap Strategi Pembelajaran Membaca untuk Siswa Sekolah Dasar - Ihwal Syafitra R; Besse Syukroni Baso (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study aims to examine the perceptions of students in the Elementary School Teacher Education (PGSD) Program at Universitas Muhammadiyah Makassar regarding reading instructional strategies implemented in elementary schools. The approach used is descriptive qualitative, with data collection techniques through semi-structured interviews and questionnaires. The respondents of this study were 32 PGSD students currently enrolled in the reading instruction course. The findings reveal that the majority of students have a positive perception of the various reading instructional strategies taught during the course. They believe that the use of diverse strategies grounded in constructivist theory, such as meaning-based word comprehension strategies and the use of interactive media, is highly effective in enhancing elementary students' reading skills. This research makes a significant contribution to the development of more relevant and effective reading instructional strategies in elementary schools and serves as a reference for teaching practices at the university level.